Guaiane sesquiterpenes from Lindera glauca: isolation, structural elucidation, and hepatoprotective effect - Lan-Lan Nie; Xin-Yu Sun; Qing Shi; Ya-Nan Duan; Jia-Yun Yang; Jin-Chang Huang; Xin-Wen Zhang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2026)

Early Jurassic tectonic–sedimentary evolution responses to large-scale salt formation in the Northern Qiangtang sub-basin: Evidence from sedimentology, geochemistry, and detrital zircon geochronology - Jun Qi; Zhongwei Wang; Jian Wang; Wangzhong Zhan; Fei Huo; Qinghua Peng; Boyu Sui; Qian Hou; Lei Li; Shangke Xie (Global and Planetary Change, 2026)

FedAD: Federated learning with generative data augmentation and adaptive parameter decomposition for rice pest and disease identification - Dongfu Hou; Bole Li; Wencan Ren; Yuan Rao; Xianhong Xie; Jun Zhu (Computers and Electronics in Agriculture, 2026)

Promoting chemical nitrogen uptake via nitrogen cycle of organisms in the rice-crayfish co-culture system - Jialu Qian; Zifang Chen; Xiaolei Gong; Jintao Li; Yishui Luo; Yali Li; Jun Hou (Aquaculture, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Fusion of hyperspectral and multisource remote sensing data using intelligent optimized ensemble learning to estimate the SOC content of seven mangrove species in China - Jun Sun; Weiguo Jiang; Ziyan Ling; Peng Hou; Zhijie Xiao; Zhe Yang; Ze Zhang; Bolin Fu; Lu Liu; Yuyang Li; Xu He (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Salinity-induced dynamics of antibiotic resistance genes across size-fractionated lifestyles: Microbial community coalescence revealed by a comprehensive source–sink framework - Guoxiang You; Chengxing Huang; Yongheng Deng; Mengting Li; Yanhong Xia; Yi Xu; Jun Hou (Environmental Pollution, 2026)

Occurrence, emissions, and risks of microplastics and plastic additives from typical municipal wastewater treatment plants effluents in China - Lizhang Wang; Jianchao Liu; Le Chen; Yiping Li; Jun Hou; Guanghua Lu (Journal of Hazardous Materials, 2026)

Towards sustainable land-use systems: Multiscale water-wetland-food trade-offs and governance pathways in China - Shuhui Lai; Weiguo Jiang; Changchun Song; Peng Hou; Xiao Li; Ze Zhang; Jun Sun; Zhijie Xiao (Journal of Cleaner Production, 2026)

Toxic effects and molecular mechanisms of Fluopyram on the liver of zebrafish (Danio rerio) - Yuqing Hou; Bo Cheng; Baihui Shi; Shuhan Li; Xuzhi Zhang; Lanjun Wang; Rui Yang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Suffocating bacterial pathogens: Material-based interventions targeting the respiratory chain - Ziyi Han; Luyi He; Jingji Hou; Wei Huang; Jun Luo; Jiaojiao Yang; Jianshu Li (Chemical Engineering Journal, 2026)

Pre-lithiation strategy enhancing interfacial stability of carbon-coated SiO anodes via controlled formation of LixSiyOz for high-energy lithium-ion batteries - Hong Dong; Yanping Ma; Xiaobin Zhou; Jinying Hou; Juan Xin; Mingzhu Wei; Jianyao Zhu; Shiyou Li; Ya-Jun Cheng (Chemical Engineering Journal, 2026)

Soil properties modulate pyroxsulam-induced oxidative stress in Eisenia fetida across contrasting soil matrices - Kaixuan Hou; Mengyuan Wang; Jiahui Dong; Chengbo Lu; Xiaole Wang; Zhongkun Du; Bing Li; Jun Wang; Jinhua Wang; Lusheng Zhu (Applied Soil Ecology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

High-level estrogen impairs memory via estrogen receptor signaling in a hypothalamic–hippocampal neural circuit - Xin Li; Nan Zang; Qianru Zhao; Yuxiang Sun; Udhaya Kumar Siva Kumar; Mengyu Hua; Wenjun Zhou; Yanyan Qi; Hu Chen; Longqing Xia; Jun Qin; Lei Sun; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

Corrigendum to “Layered Bayesian model comparison and uncertainty quantification for CPTU dissipation test inversion” [Comput. Geotech. 201 (2027) 108489] - Jingtong He; Liangfu Xie; Caijin Wang; Xuejun Liu; Jun Wang; Zhiming Liu; Xianming Hou; Yanjun Li; Tao Zhang; Annan Zhou; Songyu Liu; Guojun Cai (Computers and Geotechnics, 2026)

Optimizing nitrogen varieties improved sustainability of rice–crayfish co-culture system - Xiaolei Gong; Yishui Luo; Yali Li; Jialu Qian; Jintao Li; Jun Hou; Xuexia Wang (Nutrient Cycling in Agroecosystems, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

A Convolutional Neural Network Combining Multi-scale Convolution and Functional Connectivity for Predicting rTMS Efficacy in MUD - Yongcong Li; Jun Ma; Tian Shu; Hong Yang; Lijuan Xie; Weitao He; Chaojing Zhang; Xiaoxia Wang; Jingming Hou (Annals of Biomedical Engineering, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Continental Jurassic/Cretaceous transition in Northeast China: Stratigraphic and spatiotemporal constraints from the Hailar Basin and adjacent areas - Chong-Yang Chen; Li-Ping Yao; Pu-Jun Wang; Hai-Bo Wu; Jing-Sheng Li; Yan-Ping Hou; Yun-Fei Xue; Shu-Qin Zhang (Cretaceous Research, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

PpZAT10 inhibits PpTST1 expression to regulate sugar accumulation in peach (Prunus persica) fruit - Qinqi Liu; Beibei Feng; Liuqing Han; Dongsheng Wang; Kexin Liu; Xiaobei Wang; Nan Hou; Lei Wang; Xianbo Zheng; Xiaodong Lian; Jun Cheng; Wei Wang; et al. (Plant Science, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Review of long-term exposure to road traffic-related air pollution and mortality: Mechanism, exposure, and meta-analysis - Yating Hou; Jun Liu; Xiaolong Tang; Honghong Yi; Tiantian Li; Tong Zhu (Environmental Impact Assessment Review, 2026)

PpBRC1 negatively regulates branching via modulating GA signal transduction gene PpGID1b in peach (Prunus persica) - Yulu Wu; Yajia Zhang; Junjie Zhang; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Nan Hou; Xianbo Zheng; Jun Cheng; Wei Wang; Langlang Zhang; Xia Ye; et al. (Plant Cell Reports, 2026)

One-Time Contact-Seedling Fertilization Enhances Rice Yield and Nitrogen Uptake in Mechanical Transplantation Systems - Jintao Li; Zijuan Ding; Xiaowei Ma; Yuxian Cao; Jun Hou; Bing Cao (Journal of Soil Science and Plant Nutrition, 2026)

Hydrodynamic response prediction of tandem transfer floating hoses based on CNN-LSTM neural networks - Jun Yan; Houbin Mao; Yuanzhe Hou; Fangqiu Li; Yuanchao Yin; Hailong Lu; Zhaokuan Lu (Ocean Engineering, 2026)

Photocatalytic degradation of indoor mixed VOCs: A mini review on polar and non-polar compounds - Yingni Feng; Jun Wang; Wenjun Wang; Qian Li; Miaomiao Qu; Yun Shi; Jian meng Chen; Mei Zhang; Li’an Hou (Journal of Environmental Sciences, 2026)

Lignocellulose processing-induced pH-responsive Pickering emulsions for curcumin delivery - Zhibo Zhao; Jun Wang; Xilong Li; Jianhua Qu; Xiaohong Hou; Yudan Zhao; Qi Hu (Food Research International, 2026)

Insights into the ascorbate-glutathione cycle and methylglyoxal detoxification systems during leaf yellowing of macadamia - Weihai Yang; Yuanbao Cai; Dongliang Hou; Qianqian Ouyang; Jun Chen; Wenjun Lei; Lizhen Zeng; Xiaopeng Li; Qiusheng Xiao; Na Chen; Qin Shao (Protoplasma, 2026)

Microplastics promote N2O emissions by enhancing nitrification via ammonia-oxidizing bacteria in estuarine and coastal sediments - Xiufeng Tang; Yingyu Bao; Jun Li; Bolin Liu; Yixuan Huang; Lijun Hou; Patrick K.H. Lee; Ping Han (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Mechanistic insights into the stereoselective toxicity of chiral difenoconazole in HepG2 cells - Xuzhi Zhang; Yuchen Guo; Junpu Wang; Yuqing Hou; Lanjun Wang; Shuhan Li; Bo Cheng; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

Insights into antibiotic resistance gene dynamics during Tanfloc-induced flocculation-storage process for cyanobacteria removal in an algae-laden drinking water source - Guoxiang You; Haoyan Jin; Miao Wu; Yongnian Li; Xiuzhou You; Chengxing Huang; Yi Xu; Jun Hou (Journal of Environmental Management, 2026)

Side-deep fertilization increases rice yield and nutrient use efficiency in China: A meta-analysis - Kaiqin Yuan; Jintao Li; Zifang Chen; Xiaowei Ma; Richard W. Bell; Yuxian Cao; Jun Hou (European Journal of Agronomy, 2026)

Achieving synergistic improvements in maize yield and nitrogen use sustainability through a novel high-density production system enabled by precision stage-specific regulation - Liang Fang; Dongping Shen; Zhen Wang; Linli Zhou; Tingting Zhang; Guoqiang Zhang; Jun Xue; Ruizhi Xie; Peng Hou; Keru Wang; Bo Ming; Ling Gou; et al. (European Journal of Agronomy, 2026)

Optimizing check dams construction and afforestation for debris flows mitigation in slag and landslides- prone gullies - Liqun Lyu; Guanyu Zhou; Jun Li; Chenyou Hou; Yunqi Wang; Chao Ma; Zihan Qi; Mengzhen Xu; Zhaoyin Wang (CATENA, 2026)

Denitrification in Suspended Sediment Systems at Different Riparian Distances: Performance and Metabolism Analysis - Shang Shi; Songqi Liu; Dapeng Li; Xinrui Yan; Ziyu Li; Zikui He; Jun Hou; Yangyang Yang (Water, Air, & Soil Pollution, 2026)

Revegetation mechanisms and influence factor in alpine mining areas: a case study of the Muli mining area, Qinghai-Tibet Plateau - Kaixin Zhang; Qingqiu Hou; Haibo Feng; Linxue Ju; Jianwei Zhou; Jun Li; Ruimin Xiong; Yi Zhu; Xiaoming Zheng; Ran Li; Chunguang Wang (Plant and Soil, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Early evolution of the Meso-Tethys Ocean: Constraints from Permo-Triassic flysch deposits - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yang Wang; Li-Qiang Zhang (Gondwana Research, 2026)

CO2-Enhanced Multiphase Flow in Heterogenous Coal Measures: Thermal-Hydraulic-Mechanic (THM) Model for Enhancing Gas Co-Production with CO2 Geo-Sequestration - Li Li; Kais Ben Abdallah; Essaieb Hamdi; Bing Hou; Zhuang Cui; Derek Elsworth; Jun Liu (Fuel, 2026)

pH-responsive polyphenol–polyester composite films for active food packaging - Xin Hu; Zhen Zhang; Chen geng; Peijie Hou; Jun Wang; Yang Li; Lifang Zhang (Food Packaging and Shelf Life, 2026)

Enhanced adsorption of ketoprofen from water by the coordination defective UiO–66 - Zhilun Liu; Lei Zhao; Xu He; Shuang Lu; Ding Hou; Jun Ma; Xueyan Li; Fuqiang Guo (Environmental Research, 2026)

Glycoengineered mesenchymal stem cell exosomes with dual-tissue targeting ameliorate glycolipid metabolism in type 2 diabetes mellitus - Yingyue Xiang; Jidong Liu; Xue Liu; Nan Zang; Mengmeng Yang; Liming Wang; Jia Song; Jun Chen; Kewei Wang; Longqing Xia; Xinguo Hou; Li Chen; et al. (Chemical Engineering Journal, 2026)

Establishment of a rapid colorimetric sensor for Microcystin-LR based on specific aptamer and positively charged gold nanoparticles - Xueting Cui; Jun Wang; Tingyu Hou; Ming Cai; Luozhao Wang; Yanna Liu; Jinhua Li (Analytica Chimica Acta, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A novel strategy for improving canopy nitrogen density retrieval by deciphering saturation effects and vertical heterogeneity - Hongye Yang; Bo Ming; Chenwei Nie; Dayun Feng; Kexin Gao; Shang Gao; Jun Xue; Guoqiang Zhang; Peng Hou; Ruizhi Xie; Zhenhai Li; Xiuliang Jin; et al. (Computers and Electronics in Agriculture, 2026)

UVB-activated permanganate enables rapid emerging organic contaminants decontamination through synergistic HO• and reactive manganese species - Ping Li; Peng Su; Qixiao Lv; Qiuling Lu; Ying Xu; Xiangyang Hou; Jucai Xu; Jun Ma; Tao Yang (Water Research, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Moderate grazing strengthens the responses of plant diversity and ANPP to climatic factors in semi-arid grasslands - Jing Hou; Jun Liu; Zhiyu Liu; Yunmeng Tang; Chen Liu; Xuekai Sun; Kaimeng Wang; Huimei Zhang; Siyu Li; Ling Wang; Deli Wang; De-Hui Zeng; et al. (Agriculture, Ecosystems & Environment, 2026)

Predicting cyanobacteria removal efficiency in flocculation-DAF: Improving interpretable automated machine learning with CVAE data augmentation - Xiao Zhao; Zijun Yang; Jianjian Wei; Zixuan Wang; Cheng Cheng; Wanyi Li; Jihang Li; Yutong Zhang; You Zuo; Jun Hou (Water Research, 2026)

Ginsenoside Rk1 inhibits postharvest fruit anthracnose by disrupting reactive oxygen species (ROS) homeostasis and activating the autophagic mechanism in Colletotrichum gloeosporioides - Xin-Yv Li; Yu-Jie Liu; Xian-Hua Meng; Chu Gong; Jun-Li Yang; Yin Qiang; Jun Wang; Xiu-Dan Hou (Pesticide Biochemistry and Physiology, 2026)

Atomistic revelation of shear-stress driven oil shale kerogen degradation: ReaxFF MD decoding mechanochemical pathways for gas genesis - Jun Yang; Quanren Yan; Li Deng; Quanlin Hou; Shanlin Gao; Haiquan Tang (Fuel, 2026)

Simultaneous removal of nitrogen and manganese via autotrophic denitrification driven by iron-carbon micro-electrolysis in an upflow anaerobic sludge blanket (UASB) reactor - Hao-Nan Xiao; Jun-Cheng Han; Tong Cai; Qian-Dong Qin; Bing-Bing Li; Hou-Yun Yang; Kan Wang (Environmental Research, 2026)

Assessment on intestinal health from polylactic acid microplastics degradation on rare minnow (Gobiocypris rarus): Inflammation regulation by mitochondrial dysfunction - Liangxia Su; Xue Xia; Miaomiao Hou; Yifan Ding; Huanhuan Li; Jianwei Wang; Yongfeng He; Jun Liu (Environmental Research, 2026)

High-performance ZnFe2O4: enabling efficient pollutant degradation and potent biofilm ablation with enhanced catalytic-antimicrobial activity - Xuechao Shi; Shuxian Hou; Shujie Li; Yao Xiao; Jun Ge; Yuhan Ji; Zhiru Tao; Yimei Wang; Wanzhen Li; Weiwei Zhang; Jun Wang; Zuchun Zhao; et al. (Chemical Engineering Journal, 2026)

CDGSH Iron Sulfur Domain 1 Relieves Neuronal Ferroptosis via Activating AMPK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

RRBP1 Inhibition Reduces Microglial M1 Polarization and Inflammation-Mediated Neuronal Loss and Oxidative Stress by Regulating ERK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

Optimisation of wheatgrass extraction using composite weighting-response surface methodology with phytochemical profiling and network pharmacology-based target prediction - Yanru Wang; Weiping Li; Meijuan Hou; Jun Su; Li Wu; Qirui Dai; Zeyu Wang; Danhong Wu (Natural Product Research, 2025)

Photosensitized fluoroquinolones drive silver nanoparticle dissolution and synergistic toxicity: The role of reactive oxygen species - Yajun Tian; Tianjian Li; Yongze Liu; Yuyan Zhang; Zhe Hou; Liqiu Zhang; Jianqiang Sun; Jun Li (Water Research, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Driver factors and influence paths behind related environmental issues announced since the implementation of the national ecological and environmental protection supervision-inspection system in China - Shiyun Liu; Sijia Li; Jiayi Hou; Jun Zhang; Hongtao Liu; Lixia Wang; Dunqiu Wang (Journal of Cleaner Production, 2025)

Smart Fe3O4-Zn NPs nanoplatforms: Integrated antibacterial activity, biofilm eradication, and magnetic propulsion for medical catheter blockage - Yuhan Ji; Xuechao Shi; Shuxian Hou; Jiaqin Huang; Jun Ge; Zhiru Tao; Xinxin Liu; Guanglei Feng; Shujie Li; Yao Xiao; Yimei Wang; Fei Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Surface engineering strategies for efficient photocatalytic nitrate reduction in wastewater purification - Yizhen Zhang; Shujun Meng; Penghui Li; Xumiao Hou; Jie Mao; Xiaoqiang Cao; Xiang Cai; Jun Zhang; Michael K.H. Leung (Environmental Research, 2025)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Multi-element competitive effect for low-strain single-crystalline Ni-rich layered oxide cathode materials - Yang Li; Jun Chen; Hongxin He; Songli Liu; Hongshuai Hou (Chemical Engineering Journal, 2025)

Decoding the Chemodiversity blueprint: Chromosome-scale genome assembly unveils photosynthesis-terpenoid coordination in Cinnamomum burmanni through genomic and miRNA regulatory networks - Chen Hou; Yanling Cai; Jun Yao; Peiwu Xie; Boxiang He; Huimign Lian; Yingli Wang; Yonglin Zhong; Bing Li; Minghuai Wang; Qian Zhang (Plant Science, 2025)

Visible-light driven synergistic adsorption-photocatalysis by S-scheme CoTiO3@Cu-BDC-NH2 MOF photocatalyst for tetracycline and chromium removal - Soodamani Periyasamy; Jun Hou; Yang Li; Natrayasamy Viswanathan; Zijun Yang; Guoxiang You; Jun Wu; Zhaoqin Huang (Journal of Environmental Management, 2025)

Anti-glycation research: using anti-oxidative as indicators, screen the most promising Dendrobium from different habitats and growing environment - Huan Luo; Meng-Yao Jin; Yang-Fan Hu; Nan Yao; Zhi-Jun Zhang; He Li; Tian-Yu Hou (Food Bioscience, 2025)

Detection of Escherichia coli O157:H7 in food based on magnetic separation and hybridization chain reaction - Ming Cai; Gaihua Wang; Xueting Cui; Tingyu Hou; Jun Wang; Kun Xu; Jinhua Li (Food Control, 2025)

Multi-objective optimization control of a novel adaptive beam string structure with double rhombic struts: Experimental and simulation studies - Jun Zou; Jinyu Lu; Haichen Zhang; Zhicheng Sha; Jiangjun Hou; Na Li (Engineering Structures, 2025)

Chiral memory-guided construction of fluorinated covalent organic frameworks for efficient photocatalytic hydrogen peroxide synthesis in seawater - Linquan Hou; Xiangjing Xie; Ye Li; Ting Song; Xiayi Hu; Bei Long; Guo-Jun Deng (Chemical Engineering Journal, 2025)

Bacterial fermentation-derived peptides for biofouling control in forward osmosis - Sheng Li; Fei Hou; Abdallatif Satti Abdalrhman; Fahad Ayesh Alharthi; Mohammed Al Namazi; Jun Ma (Journal of Environmental Chemical Engineering, 2025)

Efficient carbon sequestration of calcium carbide slag based on additive regulation - Zhiyan Liu; Li Hou; Jun Li; Zhongyuan Lu (Journal of Environmental Chemical Engineering, 2025)

Systematic study of microplastics on methane production in anaerobic digestion: Performance and microbial response - Chen-Yu Li; Li Yu; Xin He; Xian-Huai Huang; Wei-Hua Li; Hou-Yun Yang; Tong-Zhan Xue; Jun Liu; Zhen Yan; Ying Hui Ong (Journal of Environmental Chemical Engineering, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Thermal p-n junctions: a macroscopic thermal diode based on heterogeneous materials - Yue Zhang; Baotong Li; Pengfei Sun; Yu Hou; Jun Hong; Meng Shi; Liang Zeng; Qingfang Liu (Chemical Engineering Journal, 2025)

Advancements in entrapment immobilization technology for enhancing Anammox process: Material effects, preparation strategy and application - Wanqi Liu; Liangang Hou; Feng Huang; Zhengwei Pan; Jun Li; Peng Tang; Yuhan Zhu; Dongyue Li; Xingrong Yao (Bioresource Technology, 2025)

RNF213 Knockdown and Inflammation Promote Angiogenesis and Phenotype Switching by JAK2/STAT3 Pathway in Moyamoya Disease - Juan Shen; Yue Wang; Yuchen Qin; Gan Chen; Jun Xu; Yunzhu Li; Yaru Hou; Yanling Liu; Wanyang Liu (Molecular Neurobiology, 2025)

Microtremor survey for exploring intermediate-to-deep geothermal resources in the urban periphery: A case study of Xining city - Sheng He; Xiao-long Han; Jing-he Li; Yu-guo Lu; De-ming Zhang; Jian-jun Hou (Applied Geophysics, 2025)

Integrating thermal vibration and local surface plasmon resonance effect boosted "Symbiotic Co-evolution" for efficient solar evaporation, antimicrobial and antibiotic resistance genes removal - Jun Guo; Jun Hou; Yanrui Wan; Zijun Yang; Yang Li; Yujiao Zhu; Kemeng Wang; Wei Ding (Water Research, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

Development of a new type of ammonia eliminator for swirl purifiers and study of its ammonia-eliminating mechanism - Jun Hou; Shihang Li; Yujie Huang; Shuda Hu; Yingchao Wei; Gan Hou; Hao Jin; Shigen Fu; Zhenjian Yu; Fubao Zhou (Process Safety and Environmental Protection, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

3,6-dibromocarbazole have a significant effect on diversity, community and function of soil microorganisms - Baihui Shi; Changrui Liu; Junpu Wang; Zhongkun Du; Kaixuan Hou; Jinhua Wang; Jun Wang; Bing Li; Lusheng Zhu (Journal of Hazardous Materials, 2025)

Zinc isotopic evidence for enhanced oceanic primary productivity during termination of the late Ediacaran Shuram Excursion - Jinzuo Tong; Meng Cheng; Jun Hu; Xinyang Chen; Haiyang Wang; Thomas J. Algeo; Mingcai Hou; Chao Li (Geochimica et Cosmochimica Acta, 2025)

Spatial confinement of Bi/TiO2 nanoparticles with an abundant heterointerface in hollow carbon spheres for durable sodium storage - Zhao Li; Rui Yuan; Yangwu Hou; Xinde Wei; Zhaozhao Zhu; Yamei Wang; Shilong Xu; Lei Chen; Yan Wang; Rui Wu; Qingquan Kong; Jun Song Chen (Chemical Engineering Journal, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Vanadyl Acetylacetonate and Berberine Synergistically Ameliorate Diabetes-induced Vascular Dysfunction and Reduce Endothelial Toxicity through ERK and Akt Regulation - Jun Sun; Ningning Shi; Xiaomin Zhang; Jiameng Dong; Lili Zhao; Tianzi Wei; Chunting Guan; Xiang Li; Xihan Yu; Congcong Hou (Biological Trace Element Research, 2025)

Oleanane-type triterpenoids from Sabia limoniacea with nitric oxide inhibitory activity - Ping Hou; Liwei Pan; Liuting Peng; Chunqiu Gan; Chenyang Ren; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanlin Cui; Wen Tang; Jun Li; Yan Huang (Phytochemistry, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

A novel graphene oxide functionalized hydrocalumite/cellulose composite for the selective and simultaneous removal of tetracycline and Cr(VI) - Soodamani Periyasamy; Jun Hou; Natrayasamy Visawanathan; Yang Li; Zijun Yang; Guoxiang You (Environmental Research, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Soil comammox Nitrospira dominates over ammonia-oxidizing archaea and bacteria in the invasion of Solidago canadensis - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Xiang-Zhen Li; Dao-Lin Du; Zhi-Cong Dai; Guang-Qian Ren; Xiao-Jun Zheng; Chao-Ying Liu (Plant and Soil, 2025)

India-Asia collisional processes: constraints from the Eocene magmatic rocks in the southern Tibetan Plateau - Li-Qiang Zhang; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yu-Jie Hao (International Geology Review, 2025)

Meroterpenoids with bicyclic polyprenylated acylphloroglucinol scaffold and anti-inflammatory activity from Hypericum lancasteri - Jin-Qiu You; Yun-Qi Jin; Yu-Meng Miao; Xin-Yu Sun; Jia-Yu Yang; Jin-Chang Huang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Mechanistic roles of long non-coding RNAs in DNA damage response and genome stability - Li Wu; Lingli Wang; Jingyu Hou; Zhengping Shao; Jun Yang; Xiangwei Gao (Mutation Research - Reviews in Mutation Research, 2025)

Emerging contaminants in Taihu lake Basin: Multi-dimensional prioritization, colloidal adsorption, and trophic-level disruptions - Huijin Cao; Jianchao Liu; Wei You; Guanghua Lu; Yiping Li; Jun Hou; Peng Gao (Journal of Environmental Management, 2025)

Development of a novel chemosensor for photodynamic antimicrobial and fluorescence-colorimetric dual-mode sensing in food preservation and spoilage process monitoring - Nan Wang; Hua-Feng Mao; Lu Wang; Yi-Miao Zhang; Jun Li; Hou-Qi Ning; Shan Qian; Xiang-Gui Chen; Xiao-Qi Yu (Food Chemistry, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Microbial denitrification responses to elevated CO2 in lake-shore sediments under different flooding conditions - Dapeng Li; Ziyu Li; Boran Xu; Tianhua Chen; Jingqiu Sun; Jun Hou; Songqi Liu (Journal of Environmental Management, 2025)

Effects of semipermeable membrane-covered composting on greenhouse gas mitigation and microbiome at different ambient temperatures at an industrial scale - Junwei Yuan; Siyuan Lin; Yi Wang; Wenxiang He; Yangyang Li; Junda Wu; Liang Cai; Xiaoyan Kong; Dongqi You; Bo Liu; Jun Hou (Journal of Environmental Chemical Engineering, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Fate and behavior of uranium biomineralization by the native Burkholderia sp. S1 isolated from tailing areas - Jun He; Yubin Hong; Yihang Zhao; Xinyu Hong; Xinye Cheng; Yongjian Xie; Qingqing Xiao; Wanrou Liu; Lihua Dong; Li’an Hou; Diyun Chen (Journal of Environmental Chemical Engineering, 2025)

Mushroom biochar-based catalysts for high-efficient activated peroxymonosulfate to degrade ketoprofen in the water - Zhilun Liu; Lei Zhao; Shuang Lu; Xiaohan Hou; Ding Hou; Bo Sun; Min Zhao; Xueyan Li; Jun Ma (Journal of Environmental Chemical Engineering, 2025)

Review on the structural design of solar-driven interfacial evaporation - Jun Hou; Yujiao Zhu; Hang Zhao; Yanrui Wan; Hanzhi Xu; Yang Li; Jun Guo; Kemeng Wang; Zijun Yang (Journal of Environmental Chemical Engineering, 2025)

Identification of the hub genes involved in ATF5 mediated stress response in vitrified mouse oocytes based on WGCNA - Guizhen Zhou; Aiju Liu; Jiachen Bai; Yixiao Zhu; Xinhua Zou; Yuwen Luo; Yizaitiguli Reyimjan; Yan Ma; Shuaixiang Huang; Yunpeng Hou; Jun Li; Xiangwei Fu (Cryobiology, 2025)

Chemical constitutes from the flower buds of Wikstroemia chamaedaphne Meissn. (Thymelaeaceae) and their chemotaxonomic significance - Yifei Liu; Tongtong Yu; Xuefen Hou; Li Li; Hai Zhu; Qi Zhang; Jun He; Lingzhi Li (Biochemical Systematics and Ecology, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Early life imidacloprid and copper exposure affects the gut microbiome, metabolism, and learning ability of honey bees (Apis mellifera) - Xijie Li; Qihe Tang; Mengshang Hou; Yantao Pang; Dan Li; Yajuan Chen; Richan Fang; Yi Deng; Jun Zhang; Chonghui Zhao; Junjie Li; Yuan Chen; et al. (Environmental Research, 2025)

Research hotspots and application of algal extracellular polymeric substances (EPS) in wastewater treatment and resources recovery - Xiang Jia; Liangang Hou; Zhengwei Pan; Wei Chen; KunKun Wang; Baiqi Fan; Jikai Lyu; Yaxin Wang; Jun Li; Xiuhong Liu (Desalination, 2025)

Three megastigmane glycosides from the stem of Mallotus barbatus - Yanling Chang; Xiaoqin Liang; Yan Huang; Chenyang Ren; Ping Hou; Liwei Pan; Jun Li (Natural Product Research, 2025)

Comammox Nitrospira are the dominant ammonia oxidizers in the Yangtze estuarine biofilms - Xiu-feng Tang; Xing-pan Guo; Lu Kuang; Xin-jie Chen; Nazupar Sidikjan; Ting-ting Xu; Shan Jiang; Min Liu; Li-jun Hou; Yi Yang (Water Research, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

Influence of hydroxyl substitution on the inhibition of flavonoids in advanced glycation end-products formation in glucose-lysine-arginine Maillard reaction models - Li-Feng Li; Meng-Di Wang; Chen-Yang Zhang; Meng-Yao Jin; Hua-Lei Chen; Huan Luo; Tian-Yu Hou; Zhi-Jun Zhang; He Li (Food Research International, 2025)

Deposited dead algae influence the microbial communities and functional potentials on the surface sediment in eutrophic shallow lakes - Yanqi Chen; Dapeng Li; Songqi Liu; Xinyu Song; Ziyu Li; Jingqiu Sun; Yao Xu; Jun Hou (Environmental Research, 2025)

From bedrock to life activity and atmospheric deposition: Drivers of soil element coupling across horizons - Yuying Wu; Yuhan Wang; Raúl Ochoa-Hueso; Enqing Hou; Jun Li; He Zhu; Jordi Sardans; Linchuan Fang; Yanhong Wu; Gan Zhang; Josep Peñuelas; Haijian Bing (Environmental Research, 2025)

Accelerated the continuous production of ROS at the concentrated alkaline solution driven by O2 microbubbles - Wenbin Hu; Huiquan Li; Chenye Wang; Xinjuan Hou; Chanjuan Zhang; Hao Du; Jun Li (Chemical Engineering Journal, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Carbon transfer from land to fluvial networks in a typical karst river-reservoir system - Yongmei Hou; Si-Liang Li; Fu-Jun Yue; Shuai Chen; Xiaolong Liu; Lishan Ran (Water Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Surfactant Enhancement in Degradation of Phenanthrene Contaminated Soil by Sodium Persulfate - Zaoquan Huang; Xiaoyuan Li; Siying Hou; Yanjie Zhao; Haijian Lu; Jun Wang; Yirong Deng (Bulletin of Environmental Contamination and Toxicology, 2025)

Improved soil organic matter monitoring by using cumulative crop residue indices derived from time-series remote sensing images in the central black soil region of China - Mei-Wei Zhang; Xiao-Lin Sun; Mei-Nan Zhang; Hao-Xuan Yang; Huan-Jun Liu; Hou-Xuan Li (Soil and Tillage Research, 2025)

Environmental drivers of biotic turnover: Insight from tectono-sedimentary environment transition during the terminal Ediacaran to Early Cambrian - Li Deng; Quanren Yan; Jun Yang; Shanlin Gao; Quanlin Hou; Haiquan Tang; Bo Song; Min Deng (Precambrian Research, 2025)

Reducing methane emissions by developing low-fumarate high-ethanol eco-friendly rice - Yunkai Jin; Tong Liu; Jia Hu; Kai Sun; Lihong Xue; Mathilde Bettembourg; Girma Bedada; Pengfu Hou; Peiying Hao; Jintian Tang; Zihong Ye; Chunlin Liu; et al. (Molecular Plant, 2025)

A novel electrochemical sensor based on La-MOF@C60-β-cyclodextrin composite for sensitive detection of dichlorophen in lake and tap water - Yu Xie; Wei Zhou; Jia-Wen Yin; Yi Li; Lin-Li Hou; Li-Min Liu; Li-Jun Liu; Kalle Salminen; Jian-Jun Sun (Journal of Environmental Chemical Engineering, 2025)

Influence of CO2 injection on characterization of microscopic pore throat structure in shale reservoirs - Xing Huang; Zhiyuan Wang; Mengqing He; Ke Wu; Longlong Chen; Xiongdi Zuo; Le Xue; Shaoqing Liu; Wenlong Hou; Xiang Li; Yiwen Wang; Jun Lu (Fuel, 2025)

Polycyclic aromatic hydrocarbons and their derivatives in sediments from the Okinawa Trough and South China Sea: Occurrence, sources, profiles, and implications for anthropogenic activities - Jin-Yun Li; Ye-Yang Hou; Wan-Jun Liao; Ying Guo; Yong He; Liang-Ying Liu (Continental Shelf Research, 2025)

Megastigmane glycoside and phenol glycosides from the bark of Mallotus barbatus - Chenyang Ren; Ping Hou; Jian Li; Yan Huang; Liwei Pan; Liuting Peng; Chunqiu Gan; Xinlan Guan; Jun Li (Natural Product Research, 2025)

Long-term effects of dead algal deposition on sediment surfaces: Behavior of endogenous phosphorus release in sediments - Yanqi Chen; Dapeng Li; Songqi Liu; Yujie Zhang; Xinrui Yan; Xinyu Song; Ziyu Li; Boling Li; Sujie Shan; Yizhi Zhu; Jun Hou (Water Research, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

The non-isothermal and isothermal pyrolysis mechanism of Longmaxi type II oil shale kerogen: A ReaxFF molecular dynamics study - Jun Yang; Quanren Yan; Li Deng; Jin Wang; Shanlin Gao; Quanlin Hou; Haiquan Tang; Bo Song; Min Deng (Fuel, 2025)

Effects of reduced flow gradient on benthic biofilm communities’ ecological network and community assembly - Lingzhan Miao; Weiyu Li; Chaoran Li; Tanveer M. Adyel; Guoxiang You; Yi Xu; Jun Wu; Yu Yao; Ming Kong; Jingjie Feng; Jun Hou (Environmental Research, 2025)

Dynamics of high-yielding maize genotypes under intensive management across multiple environments - Rongfa Li; Guoqiang Zhang; Ruizhi Xie; Peng Hou; Bo Ming; Jun Xue; Keru Wang; Shaokun Li (European Journal of Agronomy, 2025)

Liquid-solid triboelectric nanogenerator for bubbles real-time detecting - Xianzhang Wang; Yixing He; Jiaqi Shao; Yuan Liu; Liran Ma; Buzhen Su; Ruoling Deng; Mingxin Hou; Ge Chen; Jun Li (Chemical Engineering Journal, 2025)

Cascade protection strategy for anchoring atomic FeN3 sites within defect-rich wood carbon aerogel for high-performance Zn-air batteries and versatile application - Jiaojiao Sun; Mengxia Shen; A-jun Chang; Chanjuan Liang; Chuanyin Xiong; Chen Hou; Jinbao Li; Pengbo Wang; Jiayin Li; Jianfeng Huang (Chemical Engineering Journal, 2025)

Temperature differentially regulates estuarine microbial N2O production along a salinity gradient - Tie-Qiang Mao; Yong Zhang; Ya-Fei Ou; Xiao-Fei Li; Yan-Ling Zheng; Xia Liang; Min Liu; Li-Jun Hou; Hong-Po Dong (Water Research, 2024)

Distinct effects of flow intermittency on the benthic microbial diversity and their denitrification on different substrates - Lingzhan Miao; Junling Zhang; Dan Luo; Tanveer M. Adyel; Yanhui Ao; Chaoran Li; Yu Yao; Jun Wu; Guoxiang You; Jun Hou (Science of The Total Environment, 2024)

Impact of elevated CO2 on microbial communities and functions in riparian sediments: Role of pollution levels in modulating effects - Ziyu Li; Dapeng Li; Songqi Liu; Huilin Zhao; Boling Li; Sujie Shan; Yizhi Zhu; Jingqiu Sun; Jun Hou (Science of The Total Environment, 2024)

Toxic effects of microplastics (MPs) on aquatic plants and phytoremediation potential in freshwater environments - Xingrong Yao; Zuojiang Lin; Wei Chen; Zhengwei Pan; Liangang Hou; Jun Li; Dongyue Li; Wanqi Liu; Kaiyao Hu (Journal of Water Process Engineering, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Co-accumulation characteristics and interaction mechanism of microplastics and PFASs in a large shallow lake - Jianchao Liu; Yinuo Xie; Lv Zhou; Guanghua Lu; Yiping Li; Peng Gao; Jun Hou (Journal of Hazardous Materials, 2024)

Degradation of particulate matter utilizing non-thermal plasma: Evolution laws of morphological micro-nanostructure and elemental occurrence state - Yunxi Shi; Daolong Hou; Yong Luo; Zhuang Kaiqi; Yinqin Yang; Zhengping Ding; Yixi Cai; Xiaohua Li; Jun Wang; Jing Wang (Journal of Environmental Chemical Engineering, 2024)

Two-stage Mesozoic oceanic subduction and related mantle metasomatism beneath the South Qiangtang terrane with implications for post-collisional magmatism - Neng Gong; Sheng-Qiang Zhang; Hui Qi; Guo-Li Yuan; Jun Li; Gen-Hou Wang; Xiao Liang; Zhi-Bo Liu (Gondwana Research, 2024)

Advances in immobilized microbial technology and its application to wastewater treatment: A review - Liangang Hou; Kaiyao Hu; Feng Huang; Zhengwei Pan; Xiang Jia; Wanqi Liu; Xingrong Yao; Zongyi Yang; Peng Tang; Jun Li (Bioresource Technology, 2024)

Patterns of spatiotemporal variations in the hydrochemistry and controlling factors of bedrock aquifers in the northern region of the Linhuan mining area - Miao Zhang; Luwang Chen; Xiaowei Hou; Yongsheng Hu; Jie Zhang; Jun Li; Xiaoxi Yin; Xiaoping Shi; Xinyue Cai (Journal of Contaminant Hydrology, 2024)

Multifactor performance evaluation of an energy-saving methanol production process coupled refrigeration-power system driven by waste heat - Li Xia; Yue Zhang; Jing Zhao; Yan Hou; Jun Zhao; Xijun Wang; Siqi Jiang; Lei Li; Xiaoyan Sun; Shuguang Xiang; Lili Wang (Fuel, 2024)

Engineering the interfacial hetero-structure for high-current-density hydrogen evolution - Bai Xu; Jiabin Xu; Junhui Hu; Shuo Li; Yong Feng; Cheng Lu; Kunming Hou; Lina Li; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

Renal denervation ameliorates atrial remodeling in type 2 diabetic rats by regulating mitochondrial dynamics - Jun-Yu Huo; Can Hou; Xiao-Long Li; Ling Yang; Wan-Ying Jiang (Journal of Physiology and Biochemistry, 2024)

Varying soil moisture and pH with alpine meadow degradation affect nitrogen preference of dominant species - Chimin Lai; Qiwu Hu; Jianbo Sun; Chengyang Li; Xiaojie Chen; Ben Chen; Xian Xue; Ji Chen; Fujiang Hou; Gang Xu; Wuchen Du; Carly Stevens; et al. (Biology and Fertility of Soils, 2024)

Ecosystem risk-based prioritization of micropollutants in wastewater treatment plant effluents across China - Jianchao Liu; Tian Ouyang; Guanghua Lu; Ming Li; Yiping Li; Jun Hou; Chao He; Peng Gao (Water Research, 2024)

Ecological risk assessment of castor oil based waterborne polyurethane: Mechanism of anionic/cationic state selective toxicity to Eisenia fetida - Ruiquan Hou; Hao Wu; Pengrui Du; Shengnan Li; Jun Liu; Jinzhe Chang; Suqing Huang; Dongmei Cheng; Peiwen Zhang; Zhixiang Zhang (Journal of Hazardous Materials, 2024)

Unraveling the role of Mn(V)/Mn(III) in the enhanced permanganate oxidation under Vis-LED radiation - Jiamin Mai; Ge Zeng; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Xiangyang Hou; Minchao Liu; Jun Ma; Tao Yang (Science of The Total Environment, 2024)

Bird-nest inspired cellulose-based biofoam with excellent performance enabled by gas–liquid interface co-assembly and thermal welding for plastic replacement - Jianming Liao; Yansu Hou; Xi Zhang; Jun Li; Min Zhang; Yunyuan Dong; Qifu Zheng; Xiaobin Chen (Chemical Engineering Journal, 2024)

Phosphorus and selenium compounding mitigates Cr stress in peanut seedlings by enhancing growth homeostasis and antioxidant properties - Hongliang Yin; Yongping Jing; Yunqing Lin; Ningning Song; Haiying Zong; Fangli Wang; Shaojing Li; Xin Song; Hong Hou; Yuxian Shang Guan; Quanli Zong; Jun Liu (Environmental Science and Pollution Research, 2024)

Phytate-modified stainless steel with ultrahigh flux and excellent anti-fouling properties for oil-water separation - Wenjie Wu; Weijia Zhou; Shuangcheng Li; Jieyu Wan; Jun Shao; Changfeng Wan; Shuiliang Chen; Haoqing Hou (Journal of Water Process Engineering, 2024)

Effects of different proportions of fruit tree branches on nicotine content and microbial diversity during composting of tobacco waste - Xiaoping Zhu; Jiali Yuan; Haoli Qu; Fuen Hou; Chunlong Mao; Jun Lei; Xiuli Cao; Lei Li (Journal of Environmental Management, 2024)

Geometric and thermodynamic analysis of a fully meshed double-scroll compressor - Jun Wang; Zengyao Li; Ruijie Hou; Shiyang Pan; Chunji Ren; Zengli Wang (International Journal of Refrigeration, 2024)

Litoamentenes A–K, eleven undescribed cembranoids with cytotoxicity from the South China Sea soft coral Litophyton amentaceum - Yuan Zong; Jun-Jie Yang; Kai Li; Yan-Fang Pei; Hui-Yue Hou; Yue Zhang; Ci-Li Wang; Ping-Lin Li (Phytochemistry, 2024)

Functionalized ligands mediated microenvironment of Pd@UiO-66-X catalysts for ethanol upgrading to n-butanol - Yaohui He; Huanqi Gou; Danfeng Zhou; Peng Wang; Shaowen Hou; Xinhui Chen; Yixing Wang; Fenghao Guo; Mengchuan Wang; Chi Wang; Jinshu Tian; Xiaonian Li; et al. (Fuel, 2024)

Constant static pressure strategy for residential kitchen exhaust system: Deducing control parameters from required exhaust rate and non-distributed data transmission - Qianwei Liang; Yanlei Yu; Changsheng Cao; Yumei Hou; Jiaying Zhou; Jun Gao; Bin Li; Jiahua Wang (Building and Environment, 2024)

Photo-assisted natural chalcopyrite activated peracetic acid for efficient micropollutant degradation - Linqian An; Xiujuan Kong; Maoju Jiang; Wenqi Li; Qixiao Lv; Xiangyang Hou; Chenlong Liu; Peng Su; Jun Ma; Tao Yang (Water Research, 2024)

Using ultrasonic-assisted sodium bicarbonate treatment to improve the gel and rheological properties of reduced-salt pork myofibrillar protein - Zhong-Wei Wu; Xue-Yan Shang; Qin Hou; Jing-Guo Xu; Zhuang-Li Kang; Han-Jun Ma (Meat Science, 2024)

Elevated nitrogen loadings facilitate carbon dioxide emissions from urban inland waters - Yong-Mei Hou; Fu-Jun Yue; Si-Liang Li; Xiao-Long Liu (Journal of Environmental Management, 2024)

Designed synthesized step-scheme heterojunction of Bi2WO6 nanosheet supported on CuBi2O4 nanorod with remarkable photo-assisted gas sensing for N-butyl alcohol - Ji-Chao Wang; Haoran Ma; Weina Shi; Wei Li; Zhiguang Zhang; Yuxia Hou; Wanqing Zhang; Jun Chen (Journal of Environmental Chemical Engineering, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Rational design of a single-component mRNA vaccine against orthopoxvirus and SARS-CoV-2 - Yilong Yang; Xiaofan Zhao; Yu Li; Xiaodong Zai; Xinyi Wang; Yue Zhang; Xiaolin Wang; Peng Lv; Jun Zhang; Lihua Hou; Junjie Xu; Wei Chen (Science China Life Sciences, 2024)

Comparative profiling of the skin and gut microbiota during metamorphosis in Chinese spiny frogs (Quasipaa spinosa) highlights microbial communities involved in disease pathogenesis - Yang Xu; Yun Jiang; Jin-Liang Hou; Juan Li; Xing-Lang Feng; Xin-Hua Liu; De-Liang Li; Jian-Guo Xiang; Jun-Hua Li (Aquaculture, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Elucidation of the dominant factors influencing N2O emission in water-level fluctuation zones in a karst canyon reservoir, southwest China - Sai-Nan Chen; Yongmei Hou; Fu-Jun Yue; Zhifeng Yan; Xiao-Long Liu; Si-Liang Li (Science of The Total Environment, 2024)

A randomized double-blind clinical trial: Comparison of oclacitinib with a traditional Chinese herbal medicine product (Dihuang Guiqin capsule) in the treatment of canine atopic dermatitis - Jun-Jie Qin; Hao Zhu; Zhe-Wen Song; Xiao-Jiao Hou; Xiu-Min Wang; Lei Wang; Jian-Xi Li (Research in Veterinary Science, 2024)

Uniform and welded networks of silver nanowires surface-embedded on cellulose yarns with PEDOT:PSS passivation for sustainable E-textiles - Yuzhen Hou; Guangjie Song; Huailing Diao; Yuanhao Li; Jun Zhang (Chemical Engineering Journal, 2024)

Investigation into the characteristics of bagasse processed with 3C-DES and the production of chemimechanical pulp for pulp molded - Yikui Zhu; Long Li; Yansu Hou; Chuan Xu; Guoxiang Hu; Yi Man; Vasilevich Sergey Vladimirovich; Jun Li; Qingang Xiong (Journal of Cleaner Production, 2024)

Arsenic disturbs neural tube closure involving AMPK/PKB-mTORC1-mediated autophagy in mice - Xiujuan Li; Gexuan Li; Shuo Cui; Yue Hou; Zelin Li; Ziyi Yan; Tingjuan Huang; Taoran Zhao; Hongkai Su; Bingrui Zhou; Juan Zhang; Ruifang Ao; et al. (Food and Chemical Toxicology, 2024)

Integration of genome-wide association and genomic prediction for dissecting seed protein and amino acid in foxtail millet - Xiongwei Zhao; Yanhua Cao; Litao Shao; Jie Zhang; Jian Cui; Jun Shu; Juanling Wang; Mingjing Huang; Jianhua Gao; Xingchun Wang; Xukai Li; Guofang Xing; et al. (Field Crops Research, 2024)

Long Non-Coding RNA MALAT1 Protects Against Spinal Cord Injury via Suppressing microRNA-125b-5p Mediated Microglial M1 Polarization, Neuroinflammation, and Neural Apoptosis - Yuanlong Li; Hua Fan; Xiong Han; Jun Sun; Ming Ni; Xiaodan Hou; Fengqin Fang; Wei Zhang; Peizhi Ma (Molecular Neurobiology, 2024)

Temporal and spatial variations in the sub-daily precipitation structure over the Qinghai–Tibet Plateau (QTP) - Hou-Liang Lu; Jun Qiu; Meng-Jia Li; Hui-Min Zuo; Jin-Li Li; Bill X. Hu; Fang-Fang Li (Science of The Total Environment, 2024)

α-synuclein-lack expression rescues methamphetamine-induced mossy fiber degeneration in dorsal hippocampal CA3 - Jiuyang Ding; Jun Wu; Xiaotao Hou; Li Yang; Yingdong Gao; Juan Zheng; Nannan Jia; Zheng He; Hui Zhang; Chengfei Wang; Xiaolan Qi; Jiang Huang; et al. (NeuroToxicology, 2024)

Cell death induced by nicotine in human neuroblastoma SH-SY5Y cells is mainly attributed to cytoplasmic vacuolation originating from the trans-Golgi network - Jun Li; Hongjuan Wang; Huan Chen; Xiao Li; Yong Liu; Hongwei Hou; Qingyuan Hu (Food and Chemical Toxicology, 2024)

GSTP1 is a negative regulator of MAVS in the antiviral signaling against SVCV infection - Shuaibin Pei; Yingbing Wei; Zhenghao Li; Huijuan Zhong; Jinyang Dong; Zewen Yi; Ruixin Hou; Weiguang Kong; Jun Xiao; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

Evaluation of toxicity of heated tobacco products aerosol and cigarette smoke to BEAS-2B cells based on 3D biomimetic chip model - Hongjuan Wang; Fengjun Lu; Yushan Tian; Sen Zhang; Shulei Han; Yaning Fu; Jun Li; Pengxia Feng; Zhihao Shi; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2024)

Natural chalcopyrite mitigates nitrous oxide emissions in sediment from coastal wetlands - Sai Yang; Li-Jun Hou; Hong-Po Dong; Jia-Wei Zhang; Deng-Zhou Gao; Xiao-Fei Li; Yan-Ling Zheng; Xia Liang; Min Liu (Science of The Total Environment, 2024)

Separation and enrichment of tricolor phosphors in waste phosphors through liquid–liquid–powder extraction method and its benefit evaluation for recovery - Li Pang Wang; Jun Ming Hou; Yan Jhang Chen; Bu Ching Tseng; Sandhya Babel (Minerals Engineering, 2024)

Exfoliated MXene/poly-melamine-formaldehyde composite membranes for removal of heavy metals and organics from aqueous solutions - Tian-Qi Zhang; Shuang Hao; Jun-Kai Zhao; Zhi-Qian Jia; Hong-Wei Tan; Yu Yang; Li-An Hou (Journal of Hazardous Materials, 2024)

Rifting of the upper Yangtze carbonate platform: Insight from middle Permian carbonate olistostromes in the NE Sichuan basin, SW China - Li Deng; Jun Yang; Quanren Yan; Bo Song; Haiquan Tang; Zhongjin Xiang; Quanlin Hou; Shanlin Gao (Journal of Asian Earth Sciences, 2024)

Effects of conjugated interactions between Perilla seed meal proteins and different polyphenols on the structural and functional properties of proteins - Dan Wang; He Li; Tian-Yu Hou; Zhi-Jun Zhang; Hui-Zhen Li (Food Chemistry, 2024)

Structural elucidation of an active polysaccharide from Radix Puerariae lobatae and its protection against acute alcoholic liver disease - Wen Cao; Jiangping Wu; Xinya Zhao; Zixu Li; Jie Yu; Taili Shao; Xuefeng Hou; Lutan Zhou; Chunfei Wang; Guodong Wang; Jun Han (Carbohydrate Polymers, 2024)

One-time root-zone fertilization of controlled-release urea increases nitrogen use efficiency while reducing nitrogen loss risk in a ratoon rice field under two irrigation practices - Zijuan Ding; Jintao Li; Fei Huang; Ren Hu; Shaobing Peng; Jianliang Huang; Jun Hou; Jianli Zhou; Chengfang Li; Bing Su; Mingjian Xu (Nutrient Cycling in Agroecosystems, 2024)

Green, mildly synthesized bismuth-based MOF for extraction of polar glucocorticoids in environmental water - Nan Li; Juan Zheng; Lu-Dan Yu; Yuan-Jun Tong; Xinying Gong; Yu Hou; Guosheng Chen; Jianqiao Xu; Fang Zhu; Gangfeng Ouyang (Journal of Hazardous Materials, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Comparative Analysis on the Safety Characteristics of N00 Mining Method with Conventional 121 Mining Method - Ben Liu; Yajun Wang; Jun Zhang; Shilin Hou; Manchao He; Xing Wu; Hongcai Li (Geotechnical and Geological Engineering, 2024)

Changes in riverbed morphology in the middle Yangtze River (Yichang–Chenglingji) after the construction of the Three Gorges Dam - Xiaohe Lai; Jianping Jia; Yuebao Hou; Jun Jiang; Maotian Li; Jing Chen; Wen Wei (Hydrological Sciences Journal, 2023)

Effects of polyethylene microplastics with different particle sizes and concentrations on the community structure and function of periphytic biofilms - Weiyu Li; Dan Luo; Ning Yan; Lingzhan Miao; Tanveer M. Adyel; Ming Kong; Jun Hou (Journal of Environmental Chemical Engineering, 2023)

Effects of the polyhalogenated carbazoles 3-bromocarbazole and 1,3,6,8-tetrabromocarbazole on soil microbial communities - Baihui Shi; Kaixuan Hou; Chao Cheng; Yao Bai; Changrui Liu; Zhongkun Du; Jinhua Wang; Jun Wang; Bing Li; Lusheng Zhu (Environmental Research, 2023)

Cover Crops Control Weed and Improve Soil Qualities in Citrus Orchard - Hang Li; Xun Wang; Yuan Li; Yuhui Hou; Ziming Zhao; Lin Meng; Ji Liu; Jun Wang; Bo Xiong; Zhihui Wang (Journal of Soil Science and Plant Nutrition, 2023)

Preparation of chitosan-iron oxide modified sludge-based biochar for effective removal of tetracycline from water: performance and mechanism - Yangyang Yang; Shihao Li; Zhenting Zhu; Lei Wan; Xun Wang; Jun Hou; Songqi Liu; Xiulei Fan (Environmental Science and Pollution Research, 2023)

Coupled sorptive and oxidative antimony(III) removal by iron-modified biochar: Mechanisms of electron-donating capacity and reactive Fe species - Yurong Gao; Hanbo Chen; Zheng Fang; Nabeel Khan Niazi; Kwasi Adusei-Fosu; Jianhong Li; Xing Yang; Zhongzhen Liu; Nanthi S. Bolan; Bin Gao; Deyi Hou; Chenghua Sun; et al. (Environmental Pollution, 2023)

Fenton pretreatment to mitigate membrane distillation fouling during treatment of landfill leachate membrane concentrate: Performance and mechanism - Zhichao Zhao; Yong Zhang; Ling Yu; Deyin Hou; Xiaohui Wu; Kuiling Li; Jun Wang (Water Research, 2023)

Influence of humate on the degradation of chloramphenicol by sulfidated ferrihydrite under dynamic anoxic/oxic environments: A combined DFT calculation and experimental study - Yan Li; Jun Hou; Lingzhan Miao; Jun Wu; Baoshan Xing (Water Research, 2023)

Acceleration of nitrogen removal performance in a biofilm reactor augmented with Pseudomonas sp. using polycaprolactone as carbon source for treating low carbon to nitrogen wastewater - Xiujie Wang; Huimin Hou; Peizheng Liu; Liangang Hou; Tongyi Yang; Hongliang Dai; Jun Li (Bioresource Technology, 2023)

Long-term mowing reinforces connections between soil microbial and plant communities in a temperate steppe - Ren Bai; Meng Zhou; Yumeng Guo; Jun Sheng; Yujia Yuan; Qingmei Li; Longyu Hou; Wenming Bai (Plant and Soil, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Intelligent monitoring of water quality based on image analytics - Han Zhou; Jun Qiu; Hou-Liang Lu; Fang-Fang Li (Journal of Contaminant Hydrology, 2023)

Pathways to increase maize yield in Northwest China: A multi-year, multi-variety analysis - Yugang Wang; Guoqiang Zhang; Rongfa Li; Keru Wang; Bo Ming; Peng Hou; Ruizhi Xie; Jun Xue; Shaokun Li (European Journal of Agronomy, 2023)

Lobetyolin, a Q-marker isolated from Radix Platycodi, exerts protective effects on cisplatin-induced cytotoxicity in HEK293 cells - Yun-yi Hou; Si-min Qi; Jing Leng; Qiong Shen; Shan Tang; Jing-tian Zhang; Jun-nan Hu; Shuang Jiang; Wei Li (Journal of Natural Medicines, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Long-term effects of Ag NPs on denitrification in sediment: Importance of Ag NPs exposure ways in aquatic ecosystems - Songqi Liu; Lingzhan Miao; Boling Li; Sujie Shan; Dapeng Li; Jun Hou (Water Research, 2023)

Study on the wet dust collection mechanism of metal-based filter screens and the effect of its inclination angle on dust removal performance - Shuda Hu; Shihang Li; Hui Cheng; Hao Jin; Jun Hou; Changgeng Gui; Xingyue Chen; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

Research and application of self-powered induction spray dust removal system for long-distance belt conveying in underground coal mines - Jun Hou; Shihang Li; Shuda Hu; Hui Cheng; Muze Han; Changgeng Gui; Qiaosong Guo; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Phytoecdysteroids from Dianthus superbus L.: Structures and anti-neuroinflammatory evaluation - Xue-Li Hou; Yu-Qi Gao; Jing-Hui Yang; Han-Wu Liu; Meng-Meng Bai; Zhen-Hai Wu; Chun-Huan Li; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry, 2023)

Challenges and engineering application of landfill leachate concentrate treatment - Qian Li; Hanlin Cui; Yihao Li; Xin Song; Wenzong Liu; Yongxuan Wang; Haimeng Hou; Hongbo Zhang; You Li; Fan Wang; Jun Song; Hanfeng Ye; et al. (Environmental Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Reducing plastic film mulching and optimizing agronomic management can ensure food security and reduce carbon emissions in irrigated maize areas - Guoqiang Zhang; Bo Ming; Ruizhi Xie; Jianglu Chen; Peng Hou; Jun Xue; Dongping Shen; Rongfa Li; Juan Zhai; Yuanmeng Zhang; Keru Wang; Shaokun Li (Science of The Total Environment, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Correction to: Decreased sustained attention, processing speed and verbal learning memory in patients with insomnia in Chinese young and middle-aged adults: a cross-sectional study - Xie Chen; Cai-Lan Hou; Shi-Bin Wang; Zhuo-Hui Huang; Ying-Hua Huang; Xue-Li Li; Fu-Jun Jia (Sleep and Biological Rhythms, 2023)

Eukaryotes contribute more than bacteria to the recovery of freshwater ecosystem functions under different drought durations - Chaoran Li; Lingzhan Miao; Tanveer M. Adyel; Wei Huang; Jianjun Wang; Jun Wu; Jun Hou; Zhiyuan Wang (Environmental Microbiology, 2023)
Global climate change mostly impacts river ecosystems by affecting microbial biodiversity and ecological functions. Considering the high functional redundancy of microorganisms, the unknown relationship between biodiversity and ecosystem functions obstructs river ecological research, especially under the influence of increasing weather extremes, such as in intermittent rivers and ephemeral streams (IRES). Herein, dry–wet alternation experiments were conducted in artificial stream channels for 25 and 90 days of drought, both followed by 20 days of rewetting. The dynamic recovery of microbial biodiversity and ecosystem functions (represented by ecosystem metabolism and denitrification rate) were determined to analyse biodiversity–ecosystem–function (BEF) relationships after different drought durations. There was a significant difference between bacterial and eukaryotic biodiversity recovery after drought. Eukaryotic biodiversity was more sensitive to drought duration than bacterial, and the eukaryotic network was more stable under dry–wet alternations. Based on the establishment of partial least squares path models, we found that eukaryotic biodiversity has a stronger effect on ecosystem functions than bacteria after long‐term drought. Indeed, this work represents a significant step forward for further research on the ecosystem functions of IRES, especially emphasizing the importance of eukaryotic biodiversity in the BEF relationship.

Fully decouple convolutional network for damage detection of rebars in RC beams - Haowei Zhang; Kang Gao; Huiying Huang; Shitong Hou; Jun Li; Gang Wu (Engineering Structures, 2023)

Effects of Different Nitrogen Types on Nitrogen Use Efficiency, Field Water Quality, and Soil Microbial Community in the Rice–Crayfish Co-Culture System - Fei Huang; Shuo Yang; Xibin Nie; Jintao Li; Yang Hu; Xuan Li; Zijuan Ding; Jun Hou; Xuexia Wang (Journal of Soil Science and Plant Nutrition, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

Mobile thoracic intraspinal neurilemmoma - Quan Li; Xinyu Hou; Jun Li; Jia Bian (Acta Neurologica Belgica, 2023)

The effect of TiO2NPs on cloransulam-methyl toxicity to earthworm (Eisenia fetida) - Ruolin Wu; Hunan Liu; Chengbo Lu; Kaixuan Hou; Xiaole Wang; Jun Wang; Zhongkun Du; Bing Li; Lusheng Zhu; Jinhua Wang (Chemosphere, 2023)

Rapid change of erosion-deposition evolution in the Minjiang estuary, Southeast China - Xiaohe Lai; Yuebao Hou; Jianping Jia; Cheng Chen; Yan Su; Jun Jiang; Jing Chen; Maotian Li; Yan Liu (Ocean & Coastal Management, 2023)

Isolation and stereospecific synthesis of indole alkaloids with lipid-lowering effects from the marine-derived fungus Colletotrichum gloeosporioides BB4 - Qin Huang; Meng-Jiao Hao; Lai-You Wang; Feng Wu; Hou-Jin Li; Jie Yuan; Jun Xu; Taifo Mahmud; Wen-Jian Lan (Phytochemistry, 2023)

Improvement of soybean meal quality by one-step fermentation with mixed-culture based on protease activity - Chuan Wang; Xiaozhi Qiu; Rui Hou; Jun Liu; Li Li; Xiang Mao (Innovative Food Science & Emerging Technologies, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

One-off irrigation improves water and nitrogen use efficiency and productivity of wheat as mediated by nitrogen rate and tillage in drought-prone areas - Kainan Zhao; Hongtao Wang; Jinzhi Wu; Akang Liu; Xiuli Huang; Guoqiang Li; Shanwei Wu; Jun Zhang; Zhenwang Zhang; Yuanquan Hou; Zhiming Zhao; Shuang Li; et al. (Field Crops Research, 2023)

Post-earthquake reliability assessment of segmental column structures based on nonlinear model updating - Yu Xin; Zuo-Cai Wang; Jun Li; Zi-Qing Yuan; Chao Li; Wei-Chao Hou (Engineering Structures, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The effect of FeS on the fate of Cr(VI) in the presence of organic matters under dynamic anoxic/oxic conditions - Jun Hou; Zhenyu Li; Jun Xia; Zongli Huo; Jun Wu (Environmental Science and Pollution Research, 2023)

Dynamic responses of carbon metabolism of sediment microbial communities to Ag nanoparticles: Effects of the single and repeated exposure scenarios - Weiyu Li; Dan Luo; Tanveer M. Adyel; Jun Wu; Lingzhan Miao; Ming Kong; Jun Hou (Science of The Total Environment, 2023)

Megastigmane glycosides from Streblus ilicifolius (S.Vidal) Corner and their anti-inflammatory activity - Yan Huang; Liwei Pan; Yanling Chang; Xiaoqin Liang; Ping Hou; Chenyang Ren; Weifeng Xu; Ruiyun Yang; Jun Li; Buming Liu (Phytochemistry, 2023)

Reasons behind seasonal and monthly precipitation variability in the Qinghai-Tibet Plateau and its surrounding areas during 1979∼2017 - Hou-Liang Lu; Fang-Fang Li; Tong-Liang Gong; Yan-Hong Gao; Jian-Feng Li; Jun Qiu (Journal of Hydrology, 2023)

Inter-basin water diversion homogenizes microbial communities mainly through stochastic assembly processes - Nan Yang; Xing Hou; Yi Li; Huanjun Zhang; Jun Wang; Xiaodong Hu; Wenlong Zhang (Environmental Research, 2023)

The role of intercellular junction proteins in the penetration resistance of Drosophila larvae to avermectin - Li-Ping Chen; Han-Qing Jiang; Liang Luo; Jun Qiu; Xue-Jie Xing; Rui-Yan Hou; Yi-Jun Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Plant regeneration via callus-mediated organogenesis in commercial variety of Chuanbeichai No. 1 in Bupleurum chinense DC - Yuchan Li; Jun Zhao; Hua Chen; Xia Yu; Hui Li; Yu Zhang; Liang Feng; Zhe Wu; Wenlin Xie; Dabin Hou; Ma Yu (Plant Biotechnology Reports, 2023)

Temporal variability of precipitation over the Qinghai‐Tibetan Plateau and its surrounding areas in the last 40 years - Hou‐Liang Lu; Fang‐Fang Li; Tong‐Liang Gong; Yan‐Hong Gao; Jian‐Feng Li; Guang‐Qian Wang; Jun Qiu (International Journal of Climatology, 2023)
The Qinghai‐Tibet Plateau (QTP) plays a crucial role in regulating the climate and hydrology over Asia, and studies indicate that the QTP tends to be warm and humid as a whole. Although precipitation variability on the QTP has a great impact on floods, soil erosion, and droughts, it is poorly understood owing to sparse meteorological observations. This study has investigated the temporal variability of precipitation on the QTP and its surrounding areas on different time scales over the past 40 years using the standardized variability index (SVI) based on entropy as well as its changing trends. The results show that the variability of precipitation has different spatial patterns on different time scales. In general, the variability of both the precipitation days and amounts are low in the southeast and northwest corners of the plateau and high in the southwest and north. It was found that the number of light precipitation days in the high vegetation coverage area in the southeastern plateau decreased significantly, but increased greatly in the bare land and sparse vegetation coverage areas in the northern part of the plateau. Such changes are believed to be conducive for ecological restoration. Most importantly, in the southern foothills of the Himalayas, many light precipitation days have turned into moderate and heavy precipitation days, and a significant increase in annual precipitation has also been noted, which are likely to cause natural disasters considering the local topographical conditions, such as landslides and mudslides. Highlights In QTP, SVI ME in May is closer to summer mode, indicating monsoon beginning have advanced to May. Extreme precipitation significantly influences precipitation variability. Daily SVI AE decreases in grassland/barren/sparsely vegetated land, good for ecology. Light rain days increased in bare land/sparse vegetation areas, benefiting vegetation restoration. In southern Himalayas, light rain changed to moderate/heavy rain, leading to natural disasters.

Characterization of the responses of soil micro-organisms to azoxystrobin and the residue dynamics of azoxystrobin in wheat–corn rotation fields over two years - Chengbo Lu; Kaixuan Hou; Tongtong Zhou; Xiaole Wang; Jingwen Zhang; Chao Cheng; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang; Lusheng Zhu (Chemosphere, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Acylphloroglucinol-monoterpene meroterpenoids from Eucalyptus tereticornis and their inhibitory activity against ATP citrate lyase - Jin-Sheng Li; Yi-Nan Liu; Jing-Ya Li; Chun Lei; Ai-Jun Hou (Phytochemistry, 2023)

Characterization of dynamic plastisphere and their underlying effects on the aging of biodegradable and traditional plastics in freshwater ecosystems - Wanyi Li; Lingzhan Miao; Tanveer M. Adyel; Jun Wu; Yue Yu; Jun Hou (Journal of Hazardous Materials, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

Ammonia-oxidizing archaea and comammox Nitrospira clade B as freeze–thaw resistant nitrifiers in wetland soils - Xiufeng Tang; Jun Li; Dongyao Sun; Linfa Fang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2023)

Combined Organic Fertilizer and Straw Return Enhanced Summer Maize Productivity and Optimized Soil Nitrate–N distribution in Rainfed Summer Maize–Winter Wheat Rotation on the Southeast Loess Plateau - Kainan Zhao; Ming Huang; Youjun Li; Jinzhi Wu; Wenzhong Tian; Junhong Li; Yuanquan Hou; Shanwei Wu; Jun Zhang; Zhenwang Zhang; Zhiming Zhao; Golam Jalal Ahammed; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Response of Soil Bacteria of Dicranopteris dichotoma Populations to Vegetation Restoration in Red Soil Region of China - Qi-yan Li; Chen-lu Zhu; Jun-bao Yu; Xin-yi Wu; Si-qi Huang; Fan Yang; Mulualem Tigabu; Xiao-long Hou (Journal of Soil Science and Plant Nutrition, 2023)

Spatio-temporal succession of microbial communities in plastisphere and their potentials for plastic degradation in freshwater ecosystems - Lingzhan Miao; Wanyi Li; Tanveer M. Adyel; Yu Yao; Ye Deng; Jun Wu; Yongqiang Zhou; Yue Yu; Jun Hou (Water Research, 2023)

A Late Jurassic magmatic flare-up triggered by break-off of the Bangong-Nujiang Meso-Tethyan slab: Insights from Jurassic arc magmatism in South Qiangtang, Central Tibet - Neng Gong; Hui Qi; Jun Li; Guo-Li Yuan; Gen-Hou Wang; Xiao Liang; Zhi-Bo Liu (Lithos, 2023)

Temporal and spatial evolutionary trends of regional extreme precipitation under different emission scenarios: Case study of the Jialing River Basin, China - Shanghong Zhang; Wenda Li; Wenjie An; Jun Hou; Xiaoning Hou; Caihong Tang; Zhiguo Gan (Journal of Hydrology, 2023)

New insights into the effects of chlorpyrifos on soil microbes: Carbon and nitrogen cycle related microbes in wheat/maize rotation agricultural field - Kaixuan Hou; Chao Cheng; Baihui Shi; Wei Liu; Zhongkun Du; Bing Li; Jun Wang; Jinhua Wang; Lusheng Zhu (Environmental Pollution, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

A global analysis of dry matter accumulation and allocation for maize yield breakthrough from 1.0 to 25.0 Mg ha−1 - Guangzhou Liu; Yunshan Yang; Xiaoxia Guo; Wanmao Liu; Ruizhi Xie; Bo Ming; Jun Xue; Keru Wang; Shaokun Li; Peng Hou (Resources, Conservation and Recycling, 2023)

Effect of rolling point accounting for 33% on the filtration performance of fibrous filter media - Hao Jin; Shihang Li; Shuda Hu; Jun Hou; Changgeng Gui; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

Terrestrial rather than volcanic mercury inputs to the Yangtze Platform (South China) during the Ordovician-Silurian transition - Yu Liu; Yuanchun Li; Mingcai Hou; Jun Shen; Thomas J. Algeo; Junxuan Fan; Xiaolin Zhou; Qing Chen; Zongyuan Sun; Chao Li (Global and Planetary Change, 2023)

Toxicity comparison of atrazine on Eisenia fetida in artificial soil and three natural soils - Xiaoying Li; Yue Yang; Ruolin Wu; Kaixuan Hou; Samuel C. Allen; Lusheng Zhu; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Ultrastable and ultrafast 3D charge–discharge network of robust chemically coupled 1 T-MoS2/Ti3C2 MXene heterostructure for aqueous Zn-ion batteries - Fei Long; Qixiang Zhang; Junjie Shi; Li Wen; Yonghui Wu; Ziqi Ren; Zunyu Liu; Yixin Hou; Ke Mao; Ke Niu; Nishuang Liu; Zhi Zhang; et al. (Chemical Engineering Journal, 2023)

Realizing high thermoelectric performance in magnetic field-assisted solution synthesized nanoporous SnSe integrated with quantum dots - Shuang Li; Yunxiang Hou; Shihua Zhang; Yaru Gong; Suniya Siddique; Di Li; Jun Fang; Pengfei Nan; Binghui Ge; Guodong Tang (Chemical Engineering Journal, 2023)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

lncRNAs MALAT1 and LINC00657 upstream to miR-214-3p/BMP2 regulate osteogenic differentiation of human mesenchymal stem cells - Jun Li; He Zhuang; Zhe Wang; Jun Cai; Xinqiang Ma; Wenxiang Chen; Xibing Jiang; Dongsheng Zhao; Wangjun Hou; Yewei Tao (Molecular Biology Reports, 2022)

Hydrogeochemical Processes of Carboniferous Limestone Groundwater in the Yangzhuang Coal Mine, Huaibei Coalfield, China - Jie Zhang; Luwang Chen; Xiaowei Hou; Xingxing Ren; Jun Li; Yifei Chen (Mine Water and the Environment, 2022)

Changes of community composition strengthen the positive effects of nitrogen deposition on litter N:P stoichiometry in a semi-arid grassland - Shuang-Li Hou; Jun-Jie Yang; Jiang-Xia Yin; Hai-Wei Wei; Yan-Yu Hu; Zhi-Wei Zhang; Guo-Jiao Yang; Xiao-Tao Lü (Plant and Soil, 2022)

The responses of detoxification enzyme and gene expression in western flower thrips, Frankliniella occidentalis, to new challenging hosts - Wen-Bo Yue; Jun-Rui Zhi; Li Liu; Xiao-Lin Hou; Mao Ye (Arthropod-Plant Interactions, 2022)

Community structure and abundance of comammox Nitrospira in Chongming eastern intertidal sediments - Dongyao Sun; Min Liu; Lijun Hou; Mengyue Zhao; Xiufeng Tang; Qiang Zhao; Jun Li; Ping Han (Journal of Soils and Sediments, 2021)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

Interactive effects of nutrient availability, fluctuating supply, and plant parasitism on the post-invasion success of Bidens pilosa - Fang-Lei Gao; Qiao-Sheng He; Ru-Qian Xie; Jia-Hui Hou; Chen-Lu Shi; Jun-Min Li; Fei-Hai Yu (Biological Invasions, 2021)

Feasibility of nanoscale zerovalent iron-loaded sediment-based biochar (nZVI-SBC) for simultaneous removal of nitrate and phosphate: high selectivity toward dinitrogen and synergistic mechanism - Xiaohui Liu; Jia Wei; Liangang Hou; Yuhan Zhu; Yaodong Wu; Luyi Xing; Yifei Zhang; Jun Li (Environmental Science and Pollution Research, 2021)

Effect of thermal damage on mechanical behavior of a fine-grained sandstone - Xiaoshuang Li; Kun Peng; Jun Peng; Di Hou (Arabian Journal of Geosciences, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Evaluating the Friendliness of Pedestrian Footbridges Using Visibility Analysis: A Case Study in Wuhan - Jun Li; Shuang Wu; Zhiwei Luo; Jingyang Hou; Wenbo Zhang; Xueye Chen; Junru Su; Shen Ying (Journal of Geovisualization and Spatial Analysis, 2021)

Modes of exploitation of atmospheric water resources in the Qinghai–Tibet plateau - Fang‐Fang Li; Kang Zhao; Hou‐Liang Lu; Guang‐Qian Wang; Jun Qiu (International Journal of Climatology, 2021)
Known as “China's Water Tower,” the Qinghai–Tibet Plateau (QTP) becomes warm and humid in the short term but faces drought in the long term because of global climate change. Atmospheric water resources seem to be the only choice in the QTP region to alleviate drought conditions. Analysis of water vapour distribution and evaluation of exploitation modes of atmospheric water resources are carried out in this study. Different exploitation modes of atmospheric water resources including routine, selective, and emergency‐oriented exploitation are distinguished using water vapour budget and its distribution entropy. Zoning of the QTP indicates that routine exploitation, that is, long‐term, continuous, and fixed‐point exploitation, can only be carried out in its eastern part, while the middle and western parts are suitable for selective exploitation. Such entropy‐based assessment and zoning can be used as a reference for the exploitation of atmospheric water in the QTP in the future. Furthermore, the proposed zoning criteria can be used to estimate the exploitability of atmospheric water resources.

First report of Chaetomella raphigera causing brown spot on Eucalyptus urophylla × E. grandis in China - Xiu-Xiu Cao; Ji-Guang Wei; Jian-Gan Hou; Chun-Li Fan; Ji Luo; Yao-Jun Wu; Xiu-Hao Yang; Ji-Tong Luo; Xiao-Bing Yang (Journal of Plant Pathology, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Cerebral microbleeds and their influence on cognitive impairment in Dialysis patients - Yujun Qian; Ke Zheng; Haiyun Wang; Hui You; Fei Han; Jun Ni; Bo Hou; Limeng Chen; Yicheng Zhu; Feng Feng; Xuemei Li (Brain Imaging and Behavior, 2021)

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Finite element analysis of trans-lamina cribrosa pressure difference on optic nerve head biomechanics: the Beijing Intracranial and Intraocular Pressure Study - Yingyan Mao; Diya Yang; Jing Li; Jun Liu; Ruowu Hou; Zheng Zhang; Yiquan Yang; Lei Tian; Robert N. Weinreb; Ningli Wang (Science China Life Sciences, 2020)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Spatio-Temporal Variations in the Abundance and Community Structure of Nitrospira in a Tropical Bay - Tie-Qiang Mao; Yan-Qun Li; Hong-Po Dong; Wen-Na Yang; Li-Jun Hou (Current Microbiology, 2020)

Changes of plant community composition instead of soil nutrient status drive the legacy effects of historical nitrogen deposition on plant community N:P stoichiometry - Yan-Yu Hu; Hai-Wei Wei; Zhi-Wei Zhang; Shuang-Li Hou; Jun-Jie Yang; Jun-Feng Wang; Xiao-Tao Lü (Plant and Soil, 2020)

PEG modification enhances the in vivo stability of bioactive proteins immobilized on magnetic nanoparticles - Qing Xu; Jing Hou; Jun Rao; Guo-Hao Li; Yun-Long Liu; Jie Zhou (Biotechnology Letters, 2020)

Decreased sustained attention, processing speed and verbal learning memory in patients with insomnia in Chinese young and middle-aged adults: a cross-sectional study - Xie Chen; Cai-Lan Hou; Shi-Bin Wang; Zhuo-Hui Huang; Ying-Hua Huang; Xue-Li Li; Fu-Jun Jia (Sleep and Biological Rhythms, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

cDNA-AFLP analysis of differentially expressed genes during microspore embryogenesis in non-heading Chinese cabbage - Ya Zhang; Su-yan Gao; Huan-huan Liu; Xi-lin Zhang; Ai-song Zeng; Jian-jun Wang; Xi-lin Hou; Ying Li (In Vitro Cellular & Developmental Biology - Plant, 2020)

Legacy effects of nitrogen deposition on plant nutrient stoichiometry in a temperate grassland - Yan-Yu Hu; Seeta Sistla; Hai-Wei Wei; Zhi-Wei Zhang; Shuang-Li Hou; Jun-Jie Yang; Zheng-Wen Wang; Jun-Feng Wang; Xiao-Tao Lü (Plant and Soil, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Interleukin-4 signalling pathway underlies the anxiolytic effect induced by 3-deoxyadenosine - Tangxin Gao; Bai Li; Yangyang Hou; Shaolei Luo; Lei Feng; Jun Nie; Yi Ma; Le Xiao; Xu Chen; Hongkun Bao; Xianmin Lu; Feilong Huang; et al. (Psychopharmacology, 2019)

Study on the efficiency of phytoremediation of soils heavily polluted with PAHs in petroleum-contaminated sites by microorganism - Liqun Hou; Rui Liu; Na Li; Yuanyuan Dai; Jun Yan (Environmental Science and Pollution Research, 2019)

Benthic foraminiferal fauna and sediment provenance of Eocene syn-rift sequences in Taiwan: implication for onset of Asian epi-continental marginal seas off China coast - Chi-Yue Huang; Lei Shao; Ming-Huei Wang; Wei-Guang Xue; Pei-Jun Qiao; Yu-Chi Cui; Yuan-Li Hou (Marine Geophysical Research, 2019)

Mitochondrial genome of Chthamalus challengeri (Crustacea: Sessilia): gene order comparison within Chthamalidae and phylogenetic consideration within Balanomorpha - Panpan Chen; Jun Song; Xin Shen; Yuefeng Cai; Ka Hou Chu; Yongqi Li; Mei Tian (Acta Oceanologica Sinica, 2019)

Characterization and expression of melanin-concentrating hormone (MCH) in common carp (Cyprinus carpio) during fasting and reproductive cycle - Jing Xu; Fuyuan Hou; Debin Wang; Jun Li; Guangzhong Yang (Fish Physiology and Biochemistry, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Investigation of the rheological behavior of activated sludge in response to CeO2 nanoparticles and potential mechanism - Guoxiang You; Peifang Wang; Jun Hou; Chao Wang; Jin Qian; Yanhui Ao; Juan Chen; Lingzhan Miao; Yi Xu; Tao Feng; Li Tao (Environmental Science and Pollution Research, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Slit2/Robo1 signaling is involved in angiogenesis of glomerular endothelial cells exposed to a diabetic-like environment - Junhui Liu; Weiping Hou; Tao Guan; Luyao Tang; Xufei Zhu; Yi Li; Shihui Hou; Jun Zhang; Hua Chen; Yunjian Huang (Angiogenesis, 2018)

Ecosystem assessment and protection effectiveness of a tropical rainforest region in Hainan Island, China - Jun Zhai; Peng Hou; Wei Cao; Min Yang; Mingyong Cai; Jing Li (Journal of Geographical Sciences, 2018)

Effects of rice straw mulching on N2O emissions and maize productivity in a rain-fed upland - Xiao Hong Wu; Wei Wang; Xiao Li Xie; Chun Mei Yin; Hai Jun Hou (Environmental Science and Pollution Research, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

Consistent responses of litter stoichiometry to N addition across different biological organization levels in a semi-arid grassland - Shuang-Li Hou; Jiang-Xia Yin; Jun-Jie Yang; Hai-Wei Wei; Guo-Jiao Yang; Yan-Yu Hu; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2017)

Petrogenetic contrastive studies on the Mesozoic early stage ore-bearing and late stage ore-barren granites from the southern Anhui Province - Jun Yan; TianJie Hou; AiGuo Wang; DeEn Wang; DingYuan Zhang; WangFei Weng; JianMin Liu; XiaoQiang Liu; QuanZhong Li (Science China Earth Sciences, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Characterization of mitochondrial prohibitin from Boleophthalmus pectinirostris and evaluation of its possible role in spermatogenesis - Di Wang; Yong-Qiang Zhao; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2017)

Pu-erh Tea Protects the Nervous System by Inhibiting the Expression of Metabotropic Glutamate Receptor 5 - Chunjie Li; Shaomeng Chai; Yongzhi Ju; Lu Hou; Hang Zhao; Wei Ma; Tian Li; Jun Sheng; Wei Shi (Molecular Neurobiology, 2017)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

Optimization of Lipid Extraction and Determination of Fatty Acid Compositions in Edible Meats of Freshwater and Marine Shrimps - Li Zhou; Peixuan Li; Yuling Zhao; Shuang Hou; Baolei Cong; Jun Huang; Yu Ding; Xiaoxiong Zeng (Journal of Aquatic Food Product Technology, 2017)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

A new dimeric stilbene from the lianas of Gnetum parvifolium - Li-Wen Tian; Jun-Jiang Lv; Yao Liu; Lu-Yao Song; Lian-Bing Hou; Cheng Zhong; Yang Xie (Natural Product Research, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

Umbilical cord-derived mesenchymal stem cell transplantation for treating elderly vascular dementia - Yan He; Xingfang Jin; Jun Wang; Mingyao Meng; Zongliu Hou; Weimeng Tian; You Li; Wenju Wang; Yunhong Wei; Yipeng Wang; Hongqiong Meng; Xuyang Lu; et al. (Cell and Tissue Banking, 2017)

Assessment of arsenic trioxide in the heart of Gallus gallus: alterations of oxidative damage parameters, inflammatory cytokines, and cardiac enzymes - Si-Wen Li; Xiao Sun; Ying He; Ying Guo; Hong-Jing Zhao; Zhi-Jun Hou; Ming-Wei Xing (Environmental Science and Pollution Research, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Impacts of CuO nanoparticles on nitrogen removal in sequencing batch biofilm reactors after short-term and long-term exposure and the functions of natural organic matter - Jun Hou; Guoxiang You; Yi Xu; Chao Wang; Peifang Wang; Lingzhan Miao; Yanhui Ao; Yi Li; Bowen LV; Yangyang Yang (Environmental Science and Pollution Research, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Effect of cadmium exposure on antioxidant enzyme catalase in different tissues of Acrossocheilus fasciatus - Yong-Qiang Zhao; Guo-Di Liu; Cong-Cong Hou; Ying-Li Han; Jun-Quan Zhu (Molecular & Cellular Toxicology, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Effect of alginate on the aggregation kinetics of copper oxide nanoparticles (CuO NPs): bridging interaction and hetero-aggregation induced by Ca2+ - Lingzhan Miao; Chao Wang; Jun Hou; Peifang Wang; Yanhui Ao; Yi Li; Bowen Lv; Yangyang Yang; Guoxiang You; Yi Xu (Environmental Science and Pollution Research, 2016)

High-density mapping of the major FHB resistance gene Fhb7 derived from Thinopyrum ponticum and its pyramiding with Fhb1 by marker-assisted selection - Jun Guo; Xiuli Zhang; Yanlin Hou; Jinjin Cai; Xiaorong Shen; Tingting Zhou; Huihui Xu; Herbert W. Ohm; Hongwei Wang; Anfei Li; Fangpu Han; Honggang Wang; et al. (Theoretical and Applied Genetics, 2015)

Overexpression of the Monodehydroascorbate Reductase Gene from Non-heading Chinese Cabbage Reduces Ascorbate Level and Growth in Transgenic Tobacco - Jun Ren; Weike Duan; Zhongwen Chen; Shuo Zhang; Xiaoming Song; Tongkun Liu; Xilin Hou; Ying Li (Plant Molecular Biology Reporter, 2015)

Physiological response to potassium deficiency in three sweet potato (Ipomoea batatas [L.] Lam.) genotypes differing in potassium utilization efficiency - Zhong-Hou Tang; Ai-Jun Zhang; Meng Wei; Xiao-Guang Chen; Zheng-Hui Liu; Hong-Min Li; Yan-Feng Ding (Acta Physiologiae Plantarum, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Association of IgE-mediated allergen sensitivity and promoter polymorphisms of chemokine (C–C motif) ligand 5 gene in Han Chinese patients with allergic skin diseases - Ji-Chang Zhou; Yu-mei Zhu; Zheng Chen; Shan He; Shi-jie Zheng; Jun-luan Mo; Xiao-li Liu; Chun-mei Gong; Bin Hou; Hui Yang (Genes & Genomics, 2015)

Genome-wide analysis of the MADS-box gene family in Brassica rapa (Chinese cabbage) - Weike Duan; Xiaoming Song; Tongkun Liu; Zhinan Huang; Jun Ren; Xilin Hou; Ying Li (Molecular Genetics and Genomics, 2015)

Impacts of socioeconomic factors on monthly electricity consumption of China’s sectors - Jing-Li Fan; Bao-Jun Tang; Hao Yu; Yun-Bing Hou; Yi-Ming Wei (Natural Hazards, 2015)

Impact of climatic factors on monthly electricity consumption of China’s sectors - Jing-Li Fan; Bao-Jun Tang; Hao Yu; Yun-Bing Hou; Yi-Ming Wei (Natural Hazards, 2015)

Sorption behavior and modeling of endocrine-disrupting chemicals on natural sediments: role of biofilm covered on surface - Haixia Ding; Yi Li; Jun Hou; Qing Wang; Yue Wu (Environmental Science and Pollution Research, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Epidemiological situation and genetic analysis of H7N9 influenza viruses in Shanghai in 2013 - Fei-Fei Ge; Hou-Bin Ju; De-Quan Yang; Jian Liu; Jian Wang; Jun Lu; Xin Li; Wei-Yi Zhang; Pei-Hong Liu; Jin-Ping Zhou (Archives of Virology, 2014)

Biological characteristics of rat dorsal root ganglion cell and human vascular endothelial cell in mono- and co-culture - Quan Yuan; Jian-Jun Li; Chun-Hou An; Li Sun (Molecular Biology Reports, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Genome-wide identification, classification and expression analysis of the heat shock transcription factor family in Chinese cabbage - Xiaoming Song; Gaofeng Liu; Weike Duan; Tongkun Liu; Zhinan Huang; Jun Ren; Ying Li; Xilin Hou (Molecular Genetics and Genomics, 2014)

EGF Enhances ADSCs Secretion via ERK and JNK Pathways - Qiang Li; Pei-hua Li; Dian-ju Hou; Ai-jun Zhang; Chang-bo Tao; Xue-yang Li; Pei-sheng Jin (Cell Biochemistry and Biophysics, 2014)

Understanding Miocene climate evolution in Northeastern Tibet: Stable carbon and oxygen isotope records from the Western Tianshui Basin, China - Zhanfang Hou; Jijun Li; Chunhui Song; Jun Zhang; Zhengchuang Hui; Shiyue Chen; Feng Xian (Journal of Earth Science, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

GP73 is a potential marker for evaluating AIDS progression and antiretroviral therapy efficacy - Hongshan Wei; Xiaohua Hao; Boan Li; Xingwang Li; Jun Hou; Yong Qiao; Renwen Zhang; Xin Li (Molecular Biology Reports, 2013)

Influence of serum adiponectin level and SNP +45 polymorphism of adiponectin gene on myocardial fibrosis - Cheng-jun Yan; Su-mei Li; Qiang Xiao; Yan Liu; Jian Hou; Ai-fang Chen; Li-ping Xia; Xiu-chang Li (Journal of Zhejiang University-SCIENCE B, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Bis(α-furancarboxylato)oxovanadium(IV) Exerts Durable Antidiabetic Effects and Suppresses Matrix Metalloproteinase-2 Activity in Spontaneous Type 2 Diabetic KKAy Mice - Linyi Li; Lihui Gao; Shuainan Liu; Quan Liu; Sujuan Sun; Yi Huan; Caina Li; Jun Peng; Guojiang Hou; Ling Li; Weiping Liu; Zhufang Shen (Biological Trace Element Research, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Nitrate or NaCl regulates floral induction in Arabidopsis thaliana - Tongkun Liu; Ying Li; Jun Ren; Yu Qian; Xuedong Yang; Weike Duan; Xilin Hou (Biologia, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Sea ice disasters and their impacts since 2000 in Laizhou Bay of Bohai Sea, China - Xu-Liang Zhang; Zhao-Hui Zhang; Zong-Jun Xu; Ge Li; Qing Sun; Xue-Jing Hou (Natural Hazards, 2013)

Genome sequence determination and analysis of a Chinese virulent strain, LMS, of Gallid herpesvirus type 2 - Yun Cheng; Feng Cong; Yan-ping Zhang; Zhi-jie Li; Na-na Xu; Guang-yu Hou; Chang-jun Liu (Virus Genes, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

A novel cold-inducible gene from Pak-choi (Brassica campestris ssp. chinensis), BcWRKY46, enhances the cold, salt and dehydration stress tolerance in transgenic tobacco - Feng Wang; Xilin Hou; Jun Tang; Zhen Wang; Shuming Wang; Fangling Jiang; Ying Li (Molecular Biology Reports, 2012)

High level interleukin-6 in the medium of human pancreatic cancer cell culture suppresses production of neurotransmitters by PC12 cell line - Rong Li; Jian Hou; Qing Xu; Qing-Jun Liu; Yi-Jun Shen; Gary Rodin; Madeline Li (Metabolic Brain Disease, 2012)

Catalytic characteristics of plant-esterase from wheat flour - Chang-jun Hou; Kun He; Li-min Yang; Dan-qun Huo; Mei Yang; Shun Huang; Liang Zhang; Cai-hong Shen (World Journal of Microbiology and Biotechnology, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Effects of Cadmium on Absorption, Excretion, and Distribution of Nickel in Rats - Zhan Li; Jun-Ying Gu; Xian-Wen Wang; Qiao-Hui Fan; Yan-Xia Geng; Zong-Xian Jiao; Yi-Ping Hou; Wang-Suo Wu (Biological Trace Element Research, 2010)

Application of High Energy Dynamic Compaction in Coastal Reclamation Areas - Shi-Jin Feng; Wei-Hou Shui; Li-Ya Gao; Li-Jun He (Marine Georesources & Geotechnology, 2010)

Field studies of the effectiveness of dynamic compaction in coastal reclamation areas - Shi-Jin Feng; Wei-Hou Shui; Li-Ya Gao; Li-Jun He; Ke Tan (Bulletin of Engineering Geology and the Environment, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Multicentre evaluation of the Elecsys® hepatitis B surface antigen II assay for detection of HBsAg in comparison with other commercially available assays - Ji-Dong Jia; Ma Hong; Lai Wei; Xin-Xin Zhang; Yuan-Li Mao; Lan-Lan Wang; Zhi-Liang Gao; Jin-Lin Hou; Jun Zhang (Medical Microbiology and Immunology, 2009)

Allograft rejection-related gene expression in the endothelial cells of renal transplantation recipients after cytomegalovirus infection - Yang Li; Hang Yan; Wu-jun Xue; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; Xin-shun Feng; Xiao-hui Tian; He-li Xiang; Jun Hou (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)

FtsY Affects Sporulation and Antibiotic Production by whiH in Streptomyces coelicolor - Xue-Ling Shen; Hui-Jun Dong; Xiao-Ping Hou; Wen-Jun Guan; Yong-Quan Li (Current Microbiology, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Phylogeography and Origin of Sheep Breeds in Northern China - Yue-Hui Ma; Shao-Qi Rao; Shen-Jin Lu; Guan-Yu Hou; Wei-Jun Guan; Hong-Bin Li; Xia Li; Qian-Jun Zhao; Jun Guo (Conservation Genetics, 2006)

Modulation of the basal activity of N-acetylglucosaminyltransferase V by phosphatidylinositol-3-kinase/protein kinase B signaling pathway in human hepatocarcinoma cells - Hua-bei Guo; Zong-hou Shen; Chuan-xin Huang; Jun Ma; Yong Huang; Hui-li Chen (Glycoconjugate Journal, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)